Medical Research Council leukaemia trial--UKALL V: an attempt to reduce the immunosuppressive effects of therapy in childhood acute lymphoblastic leukemia. Report to the Council by the Working Party on Leukaemia in Childhood. - Chessells, J; Durrant, J; Hardy, R; Richards, S (1986)
The Medical Research Council UKALL V trial for children with standard-risk acute lymphoblastic leukemia (ALL) (aged 1 to 14 years, leucocyte count less than 20 X 10(9)/L) was designed to determine whether the immunosuppressive effects of treatment could be reduced without sacrifice of antileukemic effect by alterations in the type of continuing therapy or in fractionation of cranial irradiation. Remission was achieved in 496 children on standard induction therapy, and 309 children received 24 Gy of cranial irradiation in ten to 16 fractions over 21 days, and 174 received 21 Gy in five to nine fractions over 21 days. The type of radiotherapy administered had no influence on relapse at any site or rate of death in remission. All 496 children were randomized to receive chemotherapy for 2 or 3 years with 6-mercaptopurine and methotrexate either as a continuous (group C) or a semicontinuous (group G) regimen or as a five-day pulse every 3 weeks (group I). All groups also received vincristine and prednisolone every 6 weeks. With a minimum follow-up of almost 7 years, patients in group I had significantly fewer remission deaths (P = .025) but a much higher rate of bone marrow relapse than those in group C or G (P = .002). There was an overall benefit for 3 years of chemotherapy compared with 2 years, which in contrast to previous studies, was more apparent in girls and in patients in groups C and G. Testicular relapse occurred in 37 boys, including 19 patients off therapy, with a previously negative biopsy. The overall results confirmed the prognostic significance of initial leucocyte count, even among these standard-risk patients, while girls had a superior rate of disease-free survival, but not of hematologic remission. It is concluded that, even among standard-risk patients, the prognosis is influenced by the height of the initial leukocyte count. While alterations in the fractionation of cranial irradiation do not appear to have influenced disease-free survival, intermittent continuing chemotherapy, although less immunosuppressive, is less effective than conventional continuous therapy in the treatment of ALL. In this study, 3 years of chemotherapy appeared superior to 2 years.